Conservation-Based Spatial Planning Policy Formulation To Strengthen Tourism Districts - Budiman, Haris; Akhmaddhian, Suwari; Yuhandra, Erga (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study discusses the formulation of regional policies in the field of conservation-based spatial planning to strengthen tourism districts. The purpose of this study is to identify and analyze the factors that influence spatial planning policies in areas that have agricultural and tourism contours. This research uses a descriptive-analytical method with a qualitative approach. The results of this study indicate that there are several factors that influence conservation and tourism-based spatial planning policies in the regions, including national policies, regional policies, community needs, and regional tourism potential. Based on the results of this analysis, the researcher recommends that tourism-based spatial planning policies in the regions should be prepared by considering these factors and involving various related parties, such as the government, community, and tourism actors. In order to implement effective conservation and tourism-based spatial planning policies, the researcher also recommends forming a team or working group specifically tasked with compiling, supervising, and evaluating these policies. In addition, the researchers also suggested campaigns and outreach to the public to increase awareness and participation in maintaining and developing regional tourism.